2007
DOI: 10.1080/13691050701380018
|View full text |Cite
|
Sign up to set email alerts
|

The lives of female sex workers in Vietnam: Findings from a qualitative study

Abstract: To facilitate better understanding of the environment and power structures in which sex work in Vietnam takes place, this study examined the sex workers' social and economic lives, their working environment, social relationships and presentation of self in everyday social contacts and interactions. Thirty in-depth interviews and 14 focus groups were conducted with street-based and venue-based sex workers in the cities of Da Nang and Hanoi. Results show that sex workers live and work within a complex system inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 13 publications
5
31
0
1
Order By: Relevance
“…The data presented here demonstrate how Senegalese sex workers enact a variety of strategies to minimise stigma (avoidance, deception, discretion, passing, secrecy, selective disclosure), similar to sex workers and stigmatised groups in other social settings (Benoit et al 2005;Bowen and Bungay 2016;Cornish 2006;Koken 2012;Ngo et al 2007;Scrambler and Paoli 2008;Wong, Holroyd, and Bingham 2011). Finally, I consider the contradictory outcomes of Senegal's registration system.…”
Section: Prostitution Debates: Abolition Empowerment and Stigmamentioning
confidence: 82%
“…The data presented here demonstrate how Senegalese sex workers enact a variety of strategies to minimise stigma (avoidance, deception, discretion, passing, secrecy, selective disclosure), similar to sex workers and stigmatised groups in other social settings (Benoit et al 2005;Bowen and Bungay 2016;Cornish 2006;Koken 2012;Ngo et al 2007;Scrambler and Paoli 2008;Wong, Holroyd, and Bingham 2011). Finally, I consider the contradictory outcomes of Senegal's registration system.…”
Section: Prostitution Debates: Abolition Empowerment and Stigmamentioning
confidence: 82%
“…Due to threats of arrest in criminalised settings, sex workers frequently migrate from known, well-populated areas to isolated locales where client violence is more likely to occur and negotiation of condom use less likely (Krüsi et al 2012). In a study of female sex workers in Vietnam, the criminalised context of sex work diminished sex worker agency and contributed to almost all of the reported physical and sexual abuse by clients (Ngo et al 2007). A Canadian study concluded that there exists 'an independent association between criminalization and enforcement based approaches to sex work and raised odds of both physical and sexual violence against female sex workers' (Shannon et al 2009, 7).…”
Section: Criminalisationmentioning
confidence: 96%
“…The first reported case of HIV in Ho Chi Minh City in 1990 served to reinforce the belief that something needed to be done about the threat of negative influences, and in 1995 the Vietnamese government initiated a campaign to eliminate 'social evils' (Rydstrøm 2006(Rydstrøm , 2010Ngo et al 2007;Vijeyarasa 2010;Horton and Rydstrøm 2011;Horton 2014). Hence, in 2000, a large number of state bodies joined forces to fight HIV, including the National AIDS Committee, which was incorporated into the National Committee for AIDS, Drugs and Prostitution Prevention and Control, which already embraced 16 ministries, the mass organisations, and the Department of Social Evil Prevention and Control (Khuat, Nguyen, and Ogden 2004; National Committee for AIDS, Drugs, and Prostitution Prevention and Control 2012).…”
Section: Hiv Preventionmentioning
confidence: 90%